2022
DOI: 10.3390/ijms23105455
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan in Nutrition and Health

Abstract: Tryptophan is a rate-limiting essential amino acid and a unique building block of peptides and proteins [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 16 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The authors attributed this effect to interactions between AADC and α-synuclein, which forms in Lewy bodies and Lewy neurites during PD. Dietary factors may also influence TRP metabolite levels because TRP is an essential amino acid that humans cannot biosynthesize . The relationship between dietary TRP consumption and its levels in the body will thus affect the levels of its derived metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this effect to interactions between AADC and α-synuclein, which forms in Lewy bodies and Lewy neurites during PD. Dietary factors may also influence TRP metabolite levels because TRP is an essential amino acid that humans cannot biosynthesize . The relationship between dietary TRP consumption and its levels in the body will thus affect the levels of its derived metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with interferon alpha (IFN-α) show reduced levels of Trp, augmented levels of kynurenine (Kyn), and elevated Kyn/Trp ratio activity together with an increase in depressive symptoms ( Correia and Vale, 2022 ). An elevated Trp to kynurenine ratio, conversely, reflects endogenous adaptation to stress ( Poeggeler et al, 2022 ).…”
Section: Special Topicsmentioning
confidence: 99%
“…Food rich in L-arginine and antioxidants can exert potent anti-aging effects that increase health and fitness. Biomatrix precision supplementation uses nutrients that target the decisive metabolic pathways [40][41][42][43][44][45][46][47][48]. These are the arginine and tryptophan pathways, and they have to be rerouted [49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Chrononutrition and Synchronisationmentioning
confidence: 99%
“…Recent research has confirmed the decisive roles of these metabolic pathways in regulating and determining human health [40][41][42]. Exploring new avenues that enable active living and healthy aging by preserving our fitness throughout our entire lifetime is the ultimate aim and goal of ongoing research in the field [43][44][45][46][47][48]. The upregulation of NO bioavailability can prevent premature aging and neurodegeneration characterized by cognitive decline [49][50][51][52][53][54][55][56][57].…”
Section: Determinants Of Life and Health Spanmentioning
confidence: 99%
See 1 more Smart Citation